Becoming Human : Matter and Meaning in an Antiblack World - Jackson, Zakiyyah Iman (Book collections on Project MUSE., 2021)
The author argues that blackness disrupts our essential ideas of race, gender, and, ultimately, the human. Rewriting the pernicious, enduring relationship between blackness and animality in the history of Western science and philosophy, this title breaks open the rancorous debate between black critical theory and posthumanism. Through the cultural terrain of literature by Toni Morrison, Nalo Hopkinson, Audre Lorde, and Octavia Butler, the art of Wangechi Mutu and Ezrom Legae, and the oratory of Frederick Douglass, Zakiyyah Iman Jackson both critiques and displaces the racial logic that has dominated scientific thought since the Enlightenment. In so doing, 'Becoming Human' demonstrates that the history of racialised gender and maternity, specifically antiblackness, is indispensable to future thought on matter, materiality, animality, and posthumanism.